The relationship between organizational learning, career development and adaptive performance / Ainaa Idayu Iskandar and Nur Sharina Burhan - Iskandar, Ainaa Idayu; Burhan, Nur Sharina (2019)
Individual adaptive performance is one of the prominent behaviours needed for an organization to function effectively. This study was conducted to identify the relationship between organizational learning and career development with employees’ adaptive performance. This study was conducted at an automotive manufacturer in Malaysia in an attempt to identify the predicting factors of adaptive performance in this context. The data was analysed using multiple regression. Findings showed that there is a significant relationship between career development and an employee’s adaptive performance, whereas the results for the organizational learning showed otherwise. This paper provides better knowledge and information on how to increase adaptive performance among employees at a given setting. The findings may also contribute to the existing literature.